Asymmetric Dearomatization of β‐Naphthols through a Bifunctional‐Thiourea‐Catalyzed Michael Reaction. (14th October 2015) - Wang, Shou‐Guo; Liu, Xi‐Jia; Zhao, Qun‐Chao; Zheng, Chao; Wang, Shao‐Bo; You, Shu‐Li
Abstract: An intermolecular asymmetric dearomatization reaction of β‐naphthols with nitroethylene through a chiral‐thiourea‐catalyzed Michael reaction is described. Enantioenriched functionalized β‐naphthalenones with an all‐carbon quaternary stereogenic center could thus be easily constructed from simple naphthol derivatives in good yields and excellent enantioselectivity (up to 79 % yield, 98 % ee ). Abstract : Die intermolekulare asymmetrische Desaromatisierung von β‐Naphtholen mit Nitroethylen verläuft über eine von einem chiralen Thioharnstoff katalysierte Michael‐Reaktion. Enantiomerenangereicherte funktionalisierte β‐Naphthalenone mit einem quartären Kohlenstoffzentrum wurden in guten Ausbeuten und mit exzellenter Enantioselektivität (bis zu 79 % Ausbeute, 98 % ee ) erhalten.